Preparation and Characterization of Biodegradable Films From Sago Starch and Chitosan Blends - Ali Abdul Amir, Ali Mohamad (2004)
Several blends were prepared based on sago starch, chitosan in the presence of glycerol as a plasticizer using a solvent casting technique. The blends and their performance films were characterised by Fourier transform infrared analysis (FTIR), differential scanning calorimetry (DSC), scanning electron microscopy (SEM), and oxygen permeability test.